Broad Strokes with a Fine Brush. Pliny Pan. 25 and its Sallustian Intertexts - Krebs, Christopher B. (Histos, 2025)
Justifying the lengthy details of his thanksgiving to the emperor (Pan. 25), Pliny alludes to two programmatic statements by Sallust. He first quotes the historian’s explicit choice of narrating history in selection (carptim, Cat. 4.2) in order to reject such a selective approach in his own case; and he justifies his rejection by adapting Sallust’s silence on mighty Carthage (Iug. 19.2). Pliny thus—indirectly and wittily (both in character)—contradicts Sallust with Sallust. In sum, the passage offers further evidence of Pliny’s dialogue with historiography, his ‘combinatorial imitation’ and, more generally, art en miniature, as well as his self-fashioning.